Peran Mediasi Work Engagement Atas Hubungan Meaningfulness of Work, Ethical Climate dan Kinerja Pegawai - Intan Widya Lestari; Muchlis Mas’ud; Ana Sopanah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Employee performance is a measure of organizational progress and development, and is the key to the success of human resource management practices. This study aims to empirically test and prove the mediating role of work engagement on the relationship between meaningfulness of work and ethical climate on employee performance. This study involved the use of Partial Least Square to analyse data collected from 51 employee of Dinas Sosial Kabupaten Gresik. The sampling technique used in this research was saturation sampling method. The results of this study indicate that meaningfulness of work and ethical climate have a significant positive effect on work engagement, meaningfulness of work does not have a significant effect on employee performance, ethical climate and work engagement have a significant positive effect on employee performance. The analysis reveals that work engagement fully mediates the relationship between meaningfulness of work and employee performance, and partially mediates the relationship between ethical climate and employee performance. A good understanding of the meaningfulness of work and a positive ethical climate in the organization encourages work engagement among employees. However, the mismatch between skills and employee job descriptions, lack of employee comfort in working and lack of employee experience in the work they do means that employees cannot provide optimal performance. Ethical climate can also encourage employees to act in the best way at work, meanwhile, work engagement can encourage employee spirit.